Sicilian coin hoard data - Prag, J R W (University of Oxford, 2024)
data downloads for coin hoard data from ancient Sicily: for Greek coin hoards from http://coinhoards.org/pages/about (accessed 06.09.2023) and for Roman coin hoard data from http://numismatics.org/chrr/pages/faq (accessed 06.09.2023) .